Teacher awareness: a key factor when implementing anti-racism initiatives to support children seeking refuge and living in direct provision. - Keohane, Róisín (STER, 2022)
This article aims to highlight teacher awareness as an essential element when implementing anti-racism initiatives to support children seeking refuge and living in direct provision (DP). This is achieved by examining the concepts of anti-racism education alongside the barriers that children who live in DP face, of which teachers must be aware. "Róisín Keohane is a Newly Qualified Teacher, who finished the Bachelor of Education programme in Marino Institute of Education in June. Discussions about race and racism and the role of education in preventing racism, led her to want to investigate the systems in place in schools to combat racism. She is passionate about catering for all students in the classroom and this stimulated her interest into the challenges that face children living in direct provision, and the way in which they can be supported. The research was thought provoking, challenging and provided Róisín with the necessary skills to have an anti-racist inclusive classroom in the future."
Keywords: Primary Education; Anti-racism; Direct Provision; Education; Intercultural education; Inclusive education; Education--Ireland; Inclusion (Education)